Repeat presentations to the emergency department for non‐fatal suicidal behaviour: Perceptions of patients. (26th August 2020) - Meehan, Tom; Baker, Debra; Blyth, Deborah; Stedman, Terry
Abstract: Presentations to emergency departments (EDs) for non‐fatal suicidal behaviour (NFSB) are increasing in Australia and overseas. Our understanding of the factors contributing to this trend remains unclear. In this qualitative phenomenological study, we explored patient perceptions of their ED experience and the interventions provided. The study group comprised 10 adults who had had 3 or more presentations to the ED in a 12‐week period for NFSB. Individual interviews were conducted in person with participants and transcribed verbatim. Three broad themes emerged from analysis of the transcripts: ED – a safety net; 'treatment – what treatment!'; and maintaining ED dependence. The findings highlight a failure to understand the needs of those with NFSB and establish better ED treatment strategies and models of aftercare for this sub‐group of patients. The findings have implications for mental health nurses working with consumers in the ED and in broader case management roles.